Umar bin 'Abdul 'Aziz's Ijtihad on Zakat Management - Nazhif Dhiya’elhaq, Muhammad Ghossan; Labib, Muhammad Alfreda Daib Insan (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This research is based on the issue of ineffective zakat management. In response to this situation, a study was conducted on the concept of zakat management according to Umar bin Abdul Aziz. The purpose of this research is to provide alternative solutions to the current problems in zakat management. The research adopts a library research or literature-based method with a descriptive-analytical approach, drawing from books, journals, and other scholarly works that serve as the object of study. The primary source used in this research is the book